Tinjauan Hasil Evaluasi Pendidikan Karakter Anak dalam Pembelajaran PAI: Review of Evaluation Results of Children's Character Education in PAI Learning - Nawawi, Moh. (Institut Agama Islam Sunan Giri Ponorogo, 2024)
Islamic Religious Education (PAI) has an important role in shaping the character of students, as a moral and ethical foundation in the education system. PAI not only teaches religious knowledge, but also focuses on developing students' attitudes and behavior in accordance with Islamic teachings. Thus, character education through PAI aims to create an intellectually intelligent generation, with high moral integrity, ready to contribute positively in a complex and dynamic society. The aim of this research is to evaluate the effectiveness of children's character education in PAI learning by examining the teaching approaches used by educators, the methods applied, and the results achieved. The research method uses a qualitative approach. Data was collected through literature studies and in-depth interviews with PAI educators from various schools in Indonesia. Research findings show that the integration of character values ​​in PAI significantly improves students' morals and ethics. Students not only understand religious concepts cognitively but are also able to apply these values ​​in everyday life.